Future of Food : Maximizing Finance for Development in Agricultural Value Chains - Townsend, Robert; Ronchi, Loraine; Brett, Chris; Moses, Gene (World Bank, Washington, DC, 2018)
Current levels of investment in agricultural value chains are insufficient to achieve key development goals including ending poverty and hunger, boosting shared prosperity through more and better jobs, and better stewarding the world’s natural resources by 2030. Crowding-in private investment to help achieve these goals and optimizing the use of scarce public resources will be needed, as will the continued promotion of good governance and environmental and social sustainability. Increasing private sector investment and associated financing will require identifying and understanding market failures currently leading to the sub-optimal private provision of goods and services needed to achieve key development goals. Where the private sector is already investing in agricultural value chains, promoting responsible investment can help increase development impacts. Crowding-in more private investment requires increasing the space for private sector activity, improving the policy and regulatory environment, and considering options for using public financing to improve private incentives and to reduce transaction costs and risks, including blended finance solutions. While these actions can help induce more private investment, there is still a critical need for public resources to finance essential public goods and services such as human capital, agricultural research, and complementary public infrastructure